Discourses of 'Good Food': The commercialization of healthy and ethical eating. (March 2020) - Eriksson, Göran; Machin, David
Abstract: In many societies, governments have become concerned about diet related illnesses and the huge economic costs of managing them, disseminating information about things like eating, balanced diets and the foods we should avoid in excess. At the same time in our shops and cafes there have been a proliferation of products which carry possibilities for making more healthy choices. Yet research shows that the health-related properties these products offer are largely contradictory, confusing and more about market buzzwords than actual healthy food. And such healthy choices have tended to blur and merge with notions of ethical and moral shopping. In this introduction to a collection of articles on the discourses of good food, we look at some of the research on 'good food' showing exactly what a multimodal critical discourse perspective can contribute to the field. We show that closer analysis of product packaging, marketing, cook books, media reports and policy documents can help us to understand how commercial forces are colonizing and shaping our ideas of what it means to be healthy and also to act as good citizens.